Association between the Mallampati score and maximal mouth opening in patients with obstructive sleep apnea. Issue 2 (22nd October 2020) - Yonenaga, Kazumichi; Taga, Hitoshi; Eno, Yukiko; Watanabe, Masato; Matsuo, Akira; Itai, Shunsuke; Ono, Sachiko; Takato, Tsuyoshi
Abstract: Purpose: This study aimed to evaluate the association between the Mallampati score and other anatomical indicators, including maximal mouth opening and body mass index (BMI). We also evaluated the association between the Mallampati score and the apnea‐hypopnea index (AHI) to confirm the scores' validity in predicting obstructive sleep apnea (OSA). Methods: We recruited patients with confirmed OSA who visited JR Tokyo General Hospital for oral appliance therapy between January 2016 and June 2019. The coefficients of determination were calculated by ordinary least square regression to evaluate the association between (a) the Mallampati score and maximal mouth opening, (b) AHI and BMI, and (c) the Mallampati score and AHI. Results: We included 82 patients with an average (standard deviation) Mallampati score of 2.2 (0.9) and mouth opening capacity of 48.7 (6.5) mm. The Mallampati score was inversely associated with maximal mouth opening ( R 2  = 0.189, P  < .01). A higher BMI was associated with a higher AHI ( R 2  = 0.115, P  < .01). No significant association was found between the Mallampati score and the AHI ( R 2  = 0.01, P  = .33). Conclusion: Although we were not able to confirm the association between the Mallampati score and the AHI that was reported previously, the Mallampati score was found to be inversely associated with the extent of mouth opening.